Prevalence of oral and maxillofacial diseases diagnosed in an Oral Medicine service during a 7-year period - Amaral, Simone de Macedo; Miranda, Aguida Maria Menezes Aguiar; Santos Netto, Juliana de Noronha; Pires, Fábio Ramôa (Journal of Oral Diagnosis, 2016)
Prevalence of oral and maxillofacial diseases is highly variable depending on the region, country and source of the data. The aim of this study was to determine the prevalence of oral and maxillofacial diseases diagnosed in an Oral Medicine service during a 7-year period. All clinical charts from patients attending the service in the period were reviewed to retrieve demographic and clinical data; diagnosis were classified in groups, distributed in absolute and relative values and analyzed with respect to their frequency. A total of 1075 clinical charts were reviewed and females represented 60% of the sample. Mean age of the patients was 41 years (ranging from 1 month to 94 years old) and most patients were in their fourties to fifties. A total of 1444 oral diseases were diagnosed and the most prevalent groups were soft-tissue tumors (184 cases, 12.7%), developmental defects (161, 11.2%) and epithelial diseases (127, 8.8%). Individually, the most frequent diseases included fibrous hyperplasias (120 cases, 8.3%), candidosis (77, 5.3%), periradicular inflammatory lesions (72, 5.0%) and potentially malignant disorders (52, 3.6%). Oral carcinomas represented 2.5% of the sample (36 cases).The present results reflect the frequency of oral diseases diagnosed in a specialized service in southeastern Brazil and will allow the establishment of preventive strategies and the adequacy of the clinical services offered to the target population.